Self-Customization: Using a Portfolio to Enhance Learner Independence - Engrand-O'Hara, Marion (Linguistik Online, 2012)
This article is based on the principle that traditional in-class teaching does not have to be radically overhauled for individualised learning to take place. The premise is that students need to be trained as effective independent learners so that, having recognised a specific learning need, they are empowered to fulfil it rather than wasting time searching for the perfect bite-size course. To this effect, the FL section of RHI has been requiring a Portfolio of Independent Study from students on all courses since September 2002. The Portfolio has been developed, and constantly revised, not only as part of a learner-centred approach to teaching and a drive to increase student motivation, but also as a lifelong learning tool. Considerations such as tutors' workload and the limitations imposed by quality assurance procedures also had to be taken into account. RHI offer an Institution-Wide Language Programme, where courses last 11 weeks and can be taken as part of a degree. However, most students take them as an elective, and most are international students. With such a variety of backgrounds and needs, a learner-centred approach was a necessity. By completing a Portfolio of Independent Study, students are given a chance to take charge of their own learning by assessing their current level / capabilities; setting realistic goals for themselves; planning learning activities; selecting relevant, level-appropriate materials to work from; evaluating the effectiveness of an activity; assessing their own progress both in terms of language competence and in terms of learner-training; setting new goals for themselves and taking advantage of learning opportunities arising in daily life. Over the last eight years, we have been in tune with the students' reaction to what is seen as an unconventional learning approach. This article thus highlights the difficulties and successes of this endeavour.